In Silico Pharmacokinetic Study of Vancomycin Using PBPK Modeling and Therapeutic Drug Monitoring - Ferreira, Abigail; Martins, Helena; Oliveira, José C.; Lapa, Rui; Vale, Nuno (Current Drug Metabolism, 2021)
Background: Vancomycin has been in clinical use for nearly 50 years and remains the first-line treatment option for Gram-positive infections, including methicillin-resistant Staphylococcus aureus (MRSA). There are multiple strategies to monitor therapy and adjust the dose of this antibiotic. AUC24/MIC ratio has been demonstrated to be the best parameter to predict the effectiveness and safety of vancomycin, and a target ratio of ≥400 is recommended. Still, trough and peak serum levels at steady-state conditions have been used in clinical settings as an accurate and practical method to monitor vancomycin. Methods: In this work, we collected and analyzed clinical information of patients being treated in a hospital center in Porto (Portugal) and studied the pharmacokinetics of vancomycin in silico, developing several physiologically based pharmacokinetic (PBPK) models using simulation software GastroPlus™. Different dosages and treatment regimens were studied, and the influence of patients’ age, weight and renal function was evaluated; a simulation population was also performed. Results: A linear effect of dose and a significant influence of weight and renal function in plasmatic levels of vancomycin was observed. Conclusion: The results of this work corroborate the accumulation of vancomycin in plasma and identify some parameters that influence the pharmacokinetics of this antibiotic. The importance of therapeutic monitoring of vancomycin is highlighted, and the usefulness of in silico tools, namely PBPK modeling, is demonstrated.
Keywords: PBPK